The relationship between amino acid intake patterns and both general and central obesity - Fahimeh Alijani; Ali Ahmadi; Nakisa Mohammadpour; Shima Jazayeri; Jamileh Abolghasemi; Hossein Shahinfar; Atie Sadat Khorasanian; Shahnaz Rimaz (BMC Nutrition)
Abstract Background Obesity is a threat to public health. Dietary protein and certain amino acids (AAs) have been associated with obesity; however, the association of AAs patterns with excess body weight has not been considered, yet. We aimed to examine the relationship between patterns of AA intake and obesity. Methods This cross-sectional study was conducted on 3197 individuals aged 35 to 70 years. Sociodemographic, medical, physical activity, and anthropometric data were collected. Energy and AAs intake were obtained by food frequency questionnaire (FFQ). Factor analysis was utilized to determine the AA patterns. Using multiple logistic regression analysis, the odds ratio (OR) of obesity was calculated among individuals categorized into tertiles of the AAs patterns. Results In this study, three AA patterns were identified. The aromatic pattern consists of phenylalanine, tryptophan, proline, glutamic acid, cysteine, serine, and leucine. Five essential AAs plus tyrosine, aspartic acid, arginine, and glycine were the components of the mixed pattern, and finally, the alanine pattern with high loadings for alanine and histidine was the third one. After adjusting for confounders, individuals in the highest tertile (T3) of the aromatic pattern had lower odds of central obesity compared to those in the lowest tertile (T1) (OR = 0.72, 95% CI: 0.58–0.89; p = 0.003), whereas this association was not observed in the alanine pattern. On the contrary, general obesity showed a positive association in T3 of the alanine pattern in comparison with T1 (OR = 1.65, 95% CI: 1.02–2.67; p = 0.039). Mixed pattern was not associated with any of the obesity types. Conclusions The aromatic pattern intake may have an inverse association with central obesity, and following the alanine pattern my contribute to higher odds of general obesity. However, the elaborate relationship between AAs and adiposity warrants further investigation.